Directional Newton methods - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
In this chapter, we are concerned with the convergence of the Directional Newton method (DNM), which is used in many areas such us computer graphics and many applied sciences. We obtain weaker convergence criteria, larger convergence domains, finer error bounds, and at least as precise information of the location as in earlier studies. Therefore, we expand the applicability of DNM.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: directional Newton method; convergence; error bounds; WOS(2)